2010
DOI: 10.1080/15245004.2010.500443
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Families in the Choice of Social Marketing Strategies for Male Circumcision Services in Johannesburg, South Africa

Abstract: Male circumcision (MC) prevents HIV acquisition in males, leading to calls for extensive implementation in sub-Saharan Africa. The widespread adoption of male circumcision will require social marketing targeted at various families and family members. The objective of this article is to demonstrate the utility of conjoint analysis in the choice of social marketing strategies tailored to different populations to promote male circumcision in Johannesburg, South Africa. Seven social marketing strategies for MC wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, our previous research on social marketing for MC services indicated that all races had a preference for a national approach that saw all South Africans receive a similar service. [15] Based on these results, we deemed that it would be politically incorrect to tailor MC services based on race, and hence this was not the focus of our study (although some key differences in attitudes by race are summarized).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, our previous research on social marketing for MC services indicated that all races had a preference for a national approach that saw all South Africans receive a similar service. [15] Based on these results, we deemed that it would be politically incorrect to tailor MC services based on race, and hence this was not the focus of our study (although some key differences in attitudes by race are summarized).…”
Section: Methodsmentioning
confidence: 96%
“…[15] Despite the need for scale-up, there has been little written on the actual design of MC services and the preferences of decision makers for MC. We sought to identify design characteristics of MC services in Johannesburg, South Africa, and to estimate preferences for the identified characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we re-classified some studies that were published as CA. Upon examination of their methods, we labeled them as DCE for this review, given their use of choice tasks comparing two or more profiles [27,[37][38][39][40]. "True" CA studies involved rating or ranking of profiles individually, rather than in head-to-head comparisons.…”
Section: Preference Elicitation Methodsmentioning
confidence: 99%
“…Of the 28 studies that employed DCE, several base statistical models were reported, including conditional logit (4, 14%) [27][28][29][30], multinomial logit (5, 18%) [31][32][33][34][35][36], ordinary least-squares regression (2, 7%) [37,38], and logistic regression (1) [39]. Three (11%) reported relative impor-tance scores [32,40,41].…”
Section: Dcementioning
confidence: 99%
“…Stated-preference methods, such as conjoint analysis [45,46] and best-worst scaling (BWS) [47], offer a potentially superior alternative to simple rating and ranking methods as they ensure people have to make tradeoffs [43]. Furthermore, as these methods can utilize random utility theory (RUT), they are more consistent with economic [48] and psychological [49] theories of choice.…”
Section: Introductionmentioning
confidence: 99%